Family history is key to the interpretation of exome sequencing in the prenatal context: unexpected diagnosis of Basal Cell Nevus Syndrome. (27th May 2022) - Rinaldi, Berardo; Cesaretti, Claudia; Boito, Simona; Villa, Roberta; Guerneri, Silvana; Borzani, Irene; Rizzuti, Tommaso; Marchetti, Daniela; Conte, Giorgio; Cinnante, Claudia; Triulzi, Fabio; Persico, Nicola; et al.
Abstract: Objectives: To reach a molecular diagnosis for a family with two consecutive fetuses presenting with multiple congenital anomalies. Methods: The two fetuses underwent prenatal ultrasound, autopsy, radiologic, and genetic investigation. Genetic analysis included karyotype and array‐CGH for both fetuses and trio‐based whole exome sequencing (WES) only for the second fetus. Results: WES results, initially focusing on recessive or dominant de novo variants, were negative.However, as a result of new relevant information regarding family history, the variant c.648_651dup in the PTCH1 gene was identified as causative of the fetal phenotype. Conclusions: This case further highlights how WES data analysis and interpretation strongly rely on family history and robust genotype–phenotype correlation. This is even more relevant in the prenatal setting, where access to fetal phenotype is limited and prenatal recognition of many morbid genes is not fully explored. We also provide a detailed description of the prenatal manifestations of Basal Cell Nevus Syndrome. Key points: What's already known about this topic? The diagnosis of BCNS is usually reached postnatally and its prenatal manifestations are mostly known from familial cases What does this study add? We provide a thorough picture of the prenatal presentation of BCNS in two fetuses We underline how a comprehensive autoptic fetal examination may disclose diagnostic handles We stress that the prenatal diagnosis of BCNS may be underestimated due to the current knowledge of this condition